2021
DOI: 10.3390/s21051578
|View full text |Cite
|
Sign up to set email alerts
|

Textile Electrodes: Influence of Knitting Construction and Pressure on the Contact Impedance

Abstract: Textile electrodes, also called textrodes, for biosignal monitoring as well as electrostimulation are central for the emerging research field of smart textiles. However, so far, only the general suitability of textrodes for those areas was investigated, while the influencing parameters on the contact impedance related to the electrode construction and external factors remain rather unknown. Therefore, in this work, six different knitted electrodes, applied both wet and dry, were compared regarding the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 50 publications
0
51
0
Order By: Relevance
“…For example, Zhou et al 50 compared the performance of the same electrode construction in dry and wet conditions. They observed significantly improved stimulation comfort and motor threshold with wet electrodes; similarly, Euler et al 65 found a significantly lower skin-electrode impedance for the same textile electrode construction wetted with tap water.…”
Section: Electrolytesmentioning
confidence: 77%
See 4 more Smart Citations
“…For example, Zhou et al 50 compared the performance of the same electrode construction in dry and wet conditions. They observed significantly improved stimulation comfort and motor threshold with wet electrodes; similarly, Euler et al 65 found a significantly lower skin-electrode impedance for the same textile electrode construction wetted with tap water.…”
Section: Electrolytesmentioning
confidence: 77%
“…As impedance is frequencydependent, values from different frequencies are incomparable. Hunold et al 67 and Euler, Guo and Persson 65 presented impedances at similar frequencies (i.e. 85 and 39 Hz) for which the wet electrodes showed values in a similar range from 10.0 to 15.8 kX, while the electrode from Zhou et al 50 had a much lower presented impedance with 0.95 kX due to presenting the impedance at 1 kHz.…”
Section: Evaluation Methods and Electrical Propertiesmentioning
confidence: 91%
See 3 more Smart Citations